SIMPEG FAKULTAS TEKNIK UNIVERSITAS HALU OLEO SUB-SISTEM KEPEGAWAIAN DAN RIWAYAT JABATAN - Harley Sebastian S Mangiri; Ika Purwanti Ningrum; Muh. Yamin (semanTIK, 2016)
The purpose of the research that has been conducted by the author is  to build and design an Employee Information System of Engineering Faculty, Halu Oleo University that can maintain  officialdom data for the employees in Engineering Faculty. System that built by the author focus on processing data related to officialdom and position history such as employee personal data, education history, furlough history, training history, position history and ranks history. This System also can generate pension age limit based on the value that entered by the Admin and provides output in the form of report. The author uses Unified Modeling Language (UML) as the system modeling language, Entity Relational Diagram (ERD) as database modeling, PHP as programming language and MySQL as system database. The results of the testing that has been done on the system shows that the system can make it easier for employees to obtain information related to their own respective officialdom data, history of their respective positions and ranks, and also provide data according to their own respective needs in the form of report. Keywords— Information System, Officialdom, Position History.